"Invisible" wildlife trades: Southeast Asia's undocumented illegal trade in wild ornamental plants. (June 2015) - Phelps, J.; Webb, Edward L.
Highlights: Southeast Asia hosts a thriving illegal trade in wild-collected protected ornamental plants. Observed cross-border trade is orders of magnitude larger than government-reported CITES statistics. Improved monitoring and enforcement are essential and viable conservation interventions. Efforts to tackle trade are often focused on charismatic fauna but must expand to include flora. Abstract: Conservation and environmental management often rely heavily on official statistics, but there are often concerns over accuracy and reliability, particularly true when dealing with sensitive issues such as illegal harvest and trade. A growing number of cases highlight commercial trades in wild flora and fauna that have been undocumented in official data. Here we present the first in-depth study of the trade of wild-collected ornamental plants in continental Southeast Asia, focusing on the four largest wildlife markets in Thailand. Botanical surveys revealed a massive, previously undocumented commercial trade in wild, protected ornamental plants involving Thailand, Lao PDR and Myanmar, focusing primarily on the Orchidaceae. The results indicate that illegal trade threatens not only charismatic Southeast Asian mammals, reptiles and amphibians, but also hundreds of tropical plant species. Trade surveys identified 347 orchid species in 93 genera, including many listed as threatened. The observed cross-border trade moves plants at a rate orders of magnitude larger than government-reported statistics, and directly conflicts with official policy statement. Harvester interviews strongly indicated that wild collection was negatively affecting the majority of species they traded. Despite three decades of broad restrictions on the international trade of all wild orchids, these results highlight a major conservation challenge that has been almost completely overlooked. There is urgent need to improve botanical trade monitoring, to operationalize existing conservation commitments, and as part of a broader, multifaceted response to illegal trade. We call for increased attention to botanical trade and conservation in Southeast Asia, and argue that efforts to tackle illegal wildlife trade must ensure they include flora.